The radiographic assessments of spino-pelvic compensation using IoT-based real-time ischial pressure adjustment. Issue 5 (4th February 2022) - Sohn, Moon-Jun; Lee, Haenghwa; Lee, Byung-Jou; Koo, Hae-Won; Kim, Kwang Hyeon; Yoon, Sang-Won
Abstract : Abstract: In malalignment syndrome, the spino-pelvic alignment correction with foot orthotics can be applied only to a standing position in the coronal plane. Considering the fact that the average time Koreans spend sitting in a chair is 7.5 hours per day, studies on spino-pelvic correction in sitting position is needed. The purpose of this study is to investigate the pressure changes and radiographic assessment of spino-pelvic alignment using a chair equipped with a height-adjustable seat-plate. This study was conducted on 30 participants with spinopelvic malalignment. All participants were subjected to measure buttocks interface pressure while seated using a smart chair in three consecutive steps: 1. on initial seated, 2. on balancing seated, and then 3. on 1 hour balancing seated. Radiographically, the five spino-pelvic parameters such as shoulder height differences (SHD), iliac crest height differences (ICHD), leg length discrepancy (LLD), pelvic oblique angle (POA), and coronal imbalance were analyzed to investigate the effect of pelvic imbalance compensation on spino-pelvic alignment. Statistical analysis was performed using ANOVA and paired t test. The pressure discrepancy improvement between buttocks from 36.4 ± 32.3 mm on initial seated to 15.7 ± 20.3 mm on balancing, 12.7 ± 10.9 mm on 1hr balancing seated (Ω, P   =   .008 ). The radiographic results of pelvic imbalance compensation during seated show a statistical improvement of average SHD (from −0.9 to −0.8 mm, P  = .005) and average ICHD (from 9.5 to 2.5 mm, P  = .037). For a standing posture after use of smart chair, average SHD value (−3.0 to −1.0 mm, P  = .005), ICHD (from 1.8 to 0.8 mm, P  = .016), and average LLD value (0.8–0.1 mm, P  = .033) were statistically significant improved. Spine-pelvic malalignment can be improved by individually customized pelvic compensation using balanced seat plate height adjustments under the real-time pressure sensing and monitoring on the buttocks while seated.